Critical Review of the Implementation of Restorative Justice for Victims of Sexual Violence Crimes: A Legal Positivism Perspective of Hart - Alifah, Nur (International Journal of Educational Research & Social Sciences, 2025)
Sexual violence is a global issue that has increasingly garnered attention, with various evolving definitions, including the explanation by the World Health Organization (WHO) which states that sexual violence involves actions to obtain unwanted sexual behaviour, carried out through coercion or without the consent of the victim. In Indonesia, sexual violence was previously regulated in the Indonesian Criminal Code (KUHP), but with the development of time, Law No. 12 of 2022 concerning Sexual Violence Crimes (UU TPKS) was introduced to provide more protection for victims and more robust law enforcement. Furthermore, the application of restorative justice principles in handling Sexual Violence Crimes has begun to be considered, although this principle was initially focused on minor criminal acts. Restorative justice aims to restore relationships between the victim, offender, and society, but its application in sexual violence cases presents various challenges, including the potential to reduce the accountability of offenders and the risk of re-victimisation of the victims. This research employs a normative legal approach with analysis of the applicable regulations and the concept of H.L.A. Hart's legal positivism, which emphasises the importance of systematic law enforcement while still allowing space for flexibility, particularly in the application of restorative principles. Based on the analysis, the application of restorative justice in sexual violence cases in Indonesia needs to be carried out with great caution to ensure the protection of victims' rights and the accountability of offenders, without neglecting the importance of firm and effective law enforcement.